2018
DOI: 10.1097/gox.0000000000001922
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sinus Surgery Associated with Rhinoseptoplasty: A Case-control Study

Abstract: Objective:To examine the difference between outcomes in the administration of concurrent endoscopic sinus surgery (ESS), septoplasty (SP), and rhinoplasty (RP) and concurrent ESS and SP in 1 single surgical session.Methods:Patients who underwent concurrent ESS and SP from September 2004 to July 2015 were identified. Furthermore, patients among them who underwent functional primary RP were selected. Subjects who had been administered concurrent ESS, SP, and RP (primary RP) were matched for sex, age, sinonasal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Recent studies also show that operating room time for combined FESS and rhinoplasty surgery compared to the sum of two standalone procedures appears to be less than staged surgeries for patients who would benefit from both surgeries resulting in lesser cost burden for the patient. 19 Operating time for combined surgeries in our study ranged from 110 to 215 minutes, whereas FESS ranged from 102 to 165 minutes and rhinoplasty ranged from 46 to 138.8 minutes. [13][14][15][16] However, it is equally important to consider the technical challenges of performing FESS around an externally dissected nose, which may fracture cartilage and bone and requires careful communication and coordination between the rhinoplasty and sinus surgeons (if done separately).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Recent studies also show that operating room time for combined FESS and rhinoplasty surgery compared to the sum of two standalone procedures appears to be less than staged surgeries for patients who would benefit from both surgeries resulting in lesser cost burden for the patient. 19 Operating time for combined surgeries in our study ranged from 110 to 215 minutes, whereas FESS ranged from 102 to 165 minutes and rhinoplasty ranged from 46 to 138.8 minutes. [13][14][15][16] However, it is equally important to consider the technical challenges of performing FESS around an externally dissected nose, which may fracture cartilage and bone and requires careful communication and coordination between the rhinoplasty and sinus surgeons (if done separately).…”
Section: Discussionmentioning
confidence: 68%
“…15 This was then followed by a series of five additional case-control studies with reported outcomes. 14,[16][17][18][19] However, these studies, all of which are included in our meta-analysis, again presented conflicting results on outcomes for combined surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Marchica et al, in a matched casecontrol study, used the Rhinosinusitis Symptom Inventory to evaluate patient satisfaction in a retrospective data collection without preoperative measurements. 22 They found no differences between groups of each 20 patients with concurrent surgery or single SRPL.…”
Section: Strengths and Weaknessesmentioning
confidence: 91%
“…Lefort I osteotomy is the most common type of surgery in the field of orthognathic surgery [1]. The secondary nasolabial changes following Lefort I osteotomy are well identified and include widening of the alar base, upturning of nasal tip, thinning and straightening of the upper lip [2].…”
Section: Introductionmentioning
confidence: 99%